KEGIATAN MEMBATIK PADA ANAK USIA 7-8 TAHUN DI SANGGAR SENI DAN BUDAYA - Lina Indra Kartika (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
Batik painting is one of the art learning activities conducted in Sanggar Seni dan Budaya Jawa Jawi Java, Jakarta Selatan for the children of 7-8 years. Introducing batik paitning for the early age children is something interesting to know because this activity is also a part of cultural heritage. This research which was conducted in 2008, aimed at desacribing how batik painting is organized in Sanggar Seni dan Budaya Jawa Jawi Java. The data were collected by using observation, interview, and document study techniques. As a descriptive research, the research findings ptovided clear description of batik painting as a learning activity and gave some comments and suggestions to improve.